Digital Leadership in Educational Institutions: Media Management Strategies for 21st-Century Science Education - Syarip; Dadang (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the role of digital leadership in educational institutions as a strategic driver for effective media management in 21st-century science education. The research aims to identify key strategies through which school leaders can leverage digital tools to enhance teaching quality, foster innovation, and improve student outcomes. Using a systematic literature review, ten relevant studies were analyzed to understand the implementation, challenges, and impacts of digital leadership. The findings reveal that digital leadership is not merely the adoption of technology but a transformative process involving vision, infrastructure development, teacher empowerment, and systemic change. Effective leaders facilitate the integration of innovative media such as Canva-based video learning and gamified Learning Management Systems, contributing to the development of critical thinking, collaboration, and creativity (4C skills). However, challenges persist, including inadequate digital infrastructure—only 35% of vocational schools have sufficient facilities—and limited digital literacy among educators. Successful implementation requires proactive leadership, policy support, continuous training, and multi-stakeholder collaboration. The study concludes that digital leadership is essential for creating adaptive, inclusive, and future-ready learning environments in science education.